2004
DOI: 10.1083/jcb.200403084
|View full text |Cite
|
Sign up to set email alerts
|

Relocation of Aurora B from centromeres to the central spindle at the metaphase to anaphase transition requires MKlp2

Abstract: Mitotic kinases of the Polo and Aurora families are key regulators of chromosome segregation and cytokinesis. Here, we have investigated the role of MKlp1 and MKlp2, two vertebrate mitotic kinesins essential for cytokinesis, in the spatial regulation of the Aurora B kinase. Previously, we have demonstrated that MKlp2 recruits Polo-like kinase 1 (Plk1) to the central spindle in anaphase. We now find that in MKlp2 but not MKlp1-depleted cells the Aurora B–INCENP complex remains at the centromeres and fails to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
299
0
11

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 291 publications
(333 citation statements)
references
References 30 publications
20
299
0
11
Order By: Relevance
“…However, in vitro the Rho GAP activity of MgcRacGAP is relatively limited. (50,51) It has been reported that phosphorylation of MgcRacGAP by Aurora B kinase stimulates its Rho GAP activity, (52) and given that this kinase is activated prior to the onset of cytokinesis and localizes in the same general region as MgcRacGAP, (53) this could contribute to GTPase flux. However, based on structural considerations, the relevance of this phosphorylation event has been questioned.…”
Section: Gtpase Fluxmentioning
confidence: 99%
“…However, in vitro the Rho GAP activity of MgcRacGAP is relatively limited. (50,51) It has been reported that phosphorylation of MgcRacGAP by Aurora B kinase stimulates its Rho GAP activity, (52) and given that this kinase is activated prior to the onset of cytokinesis and localizes in the same general region as MgcRacGAP, (53) this could contribute to GTPase flux. However, based on structural considerations, the relevance of this phosphorylation event has been questioned.…”
Section: Gtpase Fluxmentioning
confidence: 99%
“…In budding yeast, the dephosphorylation of INCENP by the Cdc14 phosphatase has been shown to be important for the transfer of INCENP from the centromere to the central spindle (Pereira and Schiebel, 2003), and this might be an additional form of regulation in human cells, too (Gruneberg et al, 2004). However, how the CPC proteins target to the centromere in the first place is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been demonstrated that the relocalization of the complex from the centromere to the central spindle at the metaphase-to-anaphase transition is dependent on the mitotic kinesin Mklp2 (Gruneberg et al, 2004). In budding yeast, the dephosphorylation of INCENP by the Cdc14 phosphatase has been shown to be important for the transfer of INCENP from the centromere to the central spindle (Pereira and Schiebel, 2003), and this might be an additional form of regulation in human cells, too (Gruneberg et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…MKLP2 is crucial for the relocation of the CPC from the centromere to the central spindle (Cesario et al, 2006;Gruneberg et al, 2004;Hümmer and Mayer, 2009) and for the appropriate localisation of PLK1 to the spindle midzone (Cesario et al, 2006;Neef et al, 2003). In contrast to centralspindlin, MKLP2 localises to regions adjacent to the Flemming body during late telophase.…”
Section: Mklp2mentioning
confidence: 99%
“…Aurora B kinase, which as a CPC component controls various aspects of mitotic progression, is recruited to the central spindle by MKLP2 after anaphase onset, although it is unclear which of the CPC subunits directly interacts with MKLP2 (Gruneberg et al, 2004;Hümmer and Mayer, 2009). It also remains to be determined how the CPC is recruited to the central spindle in organisms that lack MKLP2, such as C. elegans, although a direct interaction between AIR-2 (its Aurora B orthologue) and ZEN-4 (its MKLP1 orthologue) has been reported (Severson et al, 2000).…”
Section: Interactions Between Midzone Organisers and Their Upstream Amentioning
confidence: 99%